2022
DOI: 10.1111/jsr.13797
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hippocampal functional connectivity responses to varying working memory loads following total sleep deprivation

Abstract: Sleep loss with work overload can impact human cognitive performance. However, the brain's response to an increased working memory load following total sleep deprivation (TSD) remains unclear. In the present study, we focussed on the dynamic response of the hippocampus to increased working memory load before and after total sleep deprivation of 36 h. A total of 16 male participants completed a verbal working memory task under functional magnetic resonance imaging. After wholebrain activation analysis and regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Another study demonstrated decreased FC between the left hippocampal and bilateral precentral gyri during the n-back task after acute SD, which implied a role for the precentral gyrus during the WM task [39]. Taken together, these ndings provide evidence for the role of these cerebral regions in cognitive and emotional processing after SD.…”
Section: Discussionmentioning
confidence: 76%
“…Another study demonstrated decreased FC between the left hippocampal and bilateral precentral gyri during the n-back task after acute SD, which implied a role for the precentral gyrus during the WM task [39]. Taken together, these ndings provide evidence for the role of these cerebral regions in cognitive and emotional processing after SD.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, 48–72 h of SD is the second trough period, with a 40–50% decline in cognitive function [ 3 ]. Previous studies have shown that SD can strongly impair human cognitive function, including attentional lapses [ 4 ], delayed sensations [ 5 ], impaired working memory [ 6 ], uncontrollable emotions [ 7 ], and confused thinking [ 8 ]. However, few studies have investigated the neural mechanisms underlying advanced cognitive functions, particularly risky decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…A study explored the electrophysiological mechanisms of WM alteration after TSD and showed that information replacement in WM was reduced after 36 h of TSD [ 11 ]. Two studies have demonstrated that brain regions associated with memory (e.g., hippocampus) were impaired by TSD [ 12 ], which also led to dysfunctional consolidation and reconsolidation during memorization [ 13 ]. In conclusion, a large number of studies showed that TSD has a negative impact on cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of load, one of the important factors of WM, in the relationship between TSD and WM and its neurophysiological mechanisms is not yet known. A functional magnetic resonance imaging (fMRI) study explored the brain’s response to increased WM load following TSD, finding that WM was impaired [ 12 ]. As the temporal resolution of EEG is better than that of fMRI, it is more suitable for studying electrophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%